# Derive the Secant method. The formula is c n+1 =c n − f(c n )−f(c n−1 ) f(c n )(c n −c n−1 ) where n≥1 Use a sketch as part of the solution. Do not use the formula for Newton Raphson to derive formula for Secant method.

X

Skip to content
# Derive the Secant method. The formula is c n+1 =c n − f(c n )−f(c n−1 ) f(c n )(c n −c n−1 ) where n≥1 Use a sketch as part of the solution. Do not use the formula for Newton Raphson to derive formula for Secant method.

## EXPERT ANSWER

X
##### Choose your mode of payment